Assessment of locomotion: binary interaction of features in children aged 5-6 years - Chermit K.D.; Kuprina N.K.; Klimenko A.A.; Zabolotniy A.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to study of catching a falling object provides a framework for evaluating the quality of children’s natural locomotion at the age of 5-6 years, with the binary interaction of symmetry-dissymmetry and symmetry-asymmetry serving as criteria for assessment. Methods and structure of the study. To assess the quality of motor skills, researchers have employed objective techniques that involve analyzing video footage and measuring the bioelectric activity of muscles through the recording and analysis of surface electromyography. Results and conclusions. It was discovered that at the age of five, a program is created that enables the execution of movements at a convenient speed. At the age of six, the program is modified to alter the speed and tempo of movement, with the aim of increasing it. The concept of symmetry is a complex interplay of symmetry and asymmetry. Dissymmetry is the initial phase of reducing symmetry, which can manifest as the loss of a component or minor deviations from the ideal state. Dissymmetry is a form of contradictory or partially disrupted symmetry, which can be seen as a form of unstable symmetry that retains the stability inherent in symmetry while also allowing for variation.